STEREOTYPES OF WOMAN IN THE NOVEL ALGO TAN PARECIDO AL AMOR OF CARMEN AMORAGA - COŞKUN ADIGÜZEL, Saliha Seniz (SSD Journal, 2022)
This study aims to analyze the stereotypes of woman in the novel Algo tan parecido al amor written by Carmen Amoraga, which belongs to the third decade after the transition to democracy in Spain. The analysis is carried out in the light of poststructuralist feminist literary criticism, especially Lacanian psychoanalysis. Representative of its time, the novel can be considered as an important reference in order to see the representation of woman in the contemporary Spanish society, which continues politicising sexual identity of woman and presenting restrictions established for her in the social order. The objective of this study is to find out thematically and formally how woman is constructed, especially focusing on the stereotypes of married woman and adulterous woman based on the stories of the three protagonists and those of their parents. It comes to the conclusion that the woman cannot construct herself as a female subject since the masculine, valued in masculine/feminine dichotomy on which the Western thought is based, is dominant in language as well and that she is obliged to construct herself as the man’s other.